2020
DOI: 10.1186/s12870-020-02493-2
|View full text |Cite
|
Sign up to set email alerts
|

Biochar addition alleviate the negative effects of drought and salinity stress on soybean productivity and water use efficiency

Abstract: Background: Environmental stress is a crucial factor restricting plant growth as well as crop productivity, thus influencing the agricultural sustainability. Biochar addition is proposed as an effective management to improve crop performance. However, there were few studies focused on the effect of biochar addition on crop growth and productivity under interactive effect of abiotic stress (e.g., drought and salinity). This study was conducted with a pot experiment to investigate the interaction effects of drou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 56 publications
2
38
0
Order By: Relevance
“…The application of biochar has a great potential to decrease Na + uptake and increase K + uptake. Biochar application increased cell formation and size in the root and allowed rice roots to absorb more K + and hold Na + ions away under salt stress avoiding ion toxicity, reducing the transport of Na + into the xylem isolating Na + into the vacuole [ 38 , 39 ]. Application of glycine betaine as foliar spraying improved seedling vigor, cell elongation, and growth, while enabling the plants with the developed transporter linked with the positive ion selectivity on the cell membrane and vacuole wall [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The application of biochar has a great potential to decrease Na + uptake and increase K + uptake. Biochar application increased cell formation and size in the root and allowed rice roots to absorb more K + and hold Na + ions away under salt stress avoiding ion toxicity, reducing the transport of Na + into the xylem isolating Na + into the vacuole [ 38 , 39 ]. Application of glycine betaine as foliar spraying improved seedling vigor, cell elongation, and growth, while enabling the plants with the developed transporter linked with the positive ion selectivity on the cell membrane and vacuole wall [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the meta-analysis studies broadly indicate biochar to be a suitable tool for improving crop yield in acidic and nutrientpoor soils. Contrary to the positive effects of biochar application, studies have also reported negative effects of application of biochar on the crop yield, plant growth, and nutrient availability (Jeffery et al, 2017;Sänger et al, 2017;Zhang et al, 2020). In some studies, the application of freshly prepared biochar has been reported to hinder crop yield due to the immobilization of nutrients (Ding et al, 2010;Taghizadeh-Toosi et al, 2012;Kammann et al, 2015).…”
Section: Effects Of Biochar On Plant Growth and Crop Yieldmentioning
confidence: 99%
“…Biederman and Stanley, 2013;Shareef and Zhao, 2017). On the contrary, some studies in temperate regions have reported no effect or negative effects on crop productivity (Hussain et al, 2017;Sänger et al, 2017;Cornelissen et al, 2018;Zhang et al, 2020). Moreover, the majority of literature available on biochar production, its characterization, and effects on soils are based on lab scale (pot or plot) studies; the field scale studies being very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Biochar not only improves the soil structure, fertility, and ion transfer ability but also increased the activity of microbes and nutrient holding and exchange capacity of the soil. Therefore, biochar addition is proposed as an effective management to improve crop performance [21], as supported by the results we obtained from the experiments on Ehretia asperula plants, for which all biochar treatments clearly improved the growth characteristics such as plant height; number of leaves; and dry biomasses of root, shoot and leaves. These results agree with previous data obtained by several researchers who reported that the application of biochar increased the plant height and leaf area of okra [30] and maize [31] under drought-stress conditions.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, biochar enriches the physicochemical properties, biological properties, and soil enzymatic activity of the soil, increasing the water status of plants. Several studies have revealed that biochar improves soil quality and crop productivity under limited water conditions [18][19][20][21]. However, some results also reported that biochar does not always seem to be useful for crop growth [22,23].…”
Section: Introductionmentioning
confidence: 99%